KEMAMPUAN MENYIMAK TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 13 PEKANBARU - Sri Wahyuni; Abdul Razak; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research discusses the ability to listen text explanation of students of class VIII SMP Negeri 13 Pekanbaru. The sample used in this research is 105. The method in this research is inferential statistic. The results of this study indicate the acceptance of Ho on lilifors test meaning that the data is normal and can be continued on the parametric inferential statistical test. Furthermore, t test that resulted in the acceptance of Ho means that the listening ability of grade VIII students of SMP Negeri 13 Pekanbaru is low. The low ability to listen to the explanatory text is known by comparing the hypothesis with t test results. Furthermore, a direct ANOVA test is performed which results in Ho's rejection meaning that there is a mean difference between classes or there are differences in the ability of each class. Weakness in the ANOVA Test is unidirectional to know which groups there are differences. Therefore the authors proceed with the Independent Sample Test. This test results in the rejection of Ho in each class compared. Meaning that all the classes studied have different abilities.Keywords : Listening, Text Eksplanasi.